Unlocking the Hydrolytic Mechanism of GH92 α-1,2-Mannosidases: Computation Inspires the use of C-Glycosides as Michaelis Complex Mimics - Alonso-Gil, Santiago; Parkan, Kamil; Kaminský, Jakub; Pohl, Radek; Miyazaki, Takatsugu (Chemistry (Weinheim an der Bergstrasse, Germany), 2022)
The conformational changes in a sugar moiety along the hydrolytic pathway are key to understand the mechanism of glycoside hydrolases (GHs) and to design new inhibitors. The two predominant itineraries for mannosidases go via O S2 →B2,5 →1 S5 and 3 S1 →3 H4 →1 C4 . For the CAZy family 92, the conformational itinerary was unknown. Published complexes of Bacteroides thetaiotaomicron GH92 catalyst with a S-glycoside and mannoimidazole indicate a 4 C1 →4 H5 /1 S5 →1 S5 mechanism. However, as observed with the GH125 family, S-glycosides may not act always as good mimics of GH's natural substrate. Here we present a cooperative study between computations and experiments where our results predict the E5 →B2,5 /1 S5 →1 S5 pathway for GH92 enzymes. Furthermore, we demonstrate the Michaelis complex mimicry of a new kind of C-disaccharides, whose biochemical applicability was still a chimera.
Keywords: glykosidy; mannosidasy; conformations; molekulární konformace; quantum mechanics; enzymology; glykosidhydrolasy; carbohydrates; Glycosides; inhibitors; Glycoside Hydrolases; Mannosidases; Molecular Conformation